The potential role of biochar in the removal of organic and microbial contaminants from potable and reuse water: A review. (September 2015) - Inyang, Mandu; Dickenson, Eric
Highlights: The potential role of biochar in water treatment systems was reviewed. The challenges and benefits of applying biochar in water treatment were presented. Biochar can potentially serve as a sustainable surrogate for activated carbon. Abstract: In this work, the potential benefits, economics, and challenges of applying biochar in water treatment operations to remove organic and microbial contaminants was reviewed. Minimizing the use of relatively more expensive traditional sorbents in water treatment is a motivating aspect of biochar production, e.g., $246/ton non-activated biochar to $1500/ton activated carbon. Biochar can remove organic contaminants in water, such as some pesticides (0.02–23 mg g −1 ), pharmaceutical and personal care products (0.001–59 mg g −1 ), dyes (2–104 mg g −1 ), humic acid (60 mg g −1 ), perfluorooctane sulfonate (164 mg g −1 ), and N -nitrosomodimethylamine (3 mg g −1 ). Including adsorption/filtration applications, biochar can potentially be used to inactivate Escherichia coli via disinfection, and transform 95% of 2-chlorobiphenyl via advanced oxidation processes. However, more sorption data using biochar especially at demonstration-scale, for treating potable and reuse water in adsorption/filtration applications will help establish the potential of biochars to serve as surrogates for activated carbons.